(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
PURPOSE: To know the effect of office automation on streamlining work procedures in the Ministry of Higher Education and Scientific Research / Supervisory and Scientific Calendar. The problem: Expecting a clear deficiency in not having modern technologies that enhance accuracy and speed at work and reduce excess workloads (routines) for the research organization throughout the research. Design / Methodology / Entry: The study in the independent variable represents office automation and represents the respondent variable by simplifying the work procedures that are related to the study plan and assumptions.) For the purpose of calculating percentages, iterations, standard deviations and arithmetic mean for all dimensions of the study, as well as testing the study hypotheses as well as using descriptive statistical analysis in that. Results: The study reached a set of conclusions, the most prominent of which is the presence of an impact, and you have to automate offices in promoting simplification of work procedures.